2020
DOI: 10.7759/cureus.7136
|View full text |Cite
|
Sign up to set email alerts
|

The Right Anterior Thoracotomy Approach to Resect a Cardiac Papillary Fibroelastoma of the Aortic Valve

Abstract: A cardiac papillary fibroelastoma (CPFE) is reported to be the second most common cardiac neoplasm after myxoma cordis. CPFEs are histologically benign, frequently asymptomatic, but highly thrombogenic, which could lead to systemic and peripheral embolization. We present a case of a 68-year-old-patient, with a history of angioosteohypertrophy syndrome, who presented at our emergency department (ED) with symptoms of transient ischemic attacks. A thorough investigation, including echocardiography, revealed a neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…Our observations indicate that the utilization of a minimally invasive approach in managing PFE resulted in favorable outcomes for these two cases. In comparison to other authors, the length of hospitalization observed in our study is nearly equivalent [ 1 , 13 ]. In our experience, we posit that the optimal therapeutic approach for treating PFE in specific patient subpopulations is minimally invasive surgery.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Our observations indicate that the utilization of a minimally invasive approach in managing PFE resulted in favorable outcomes for these two cases. In comparison to other authors, the length of hospitalization observed in our study is nearly equivalent [ 1 , 13 ]. In our experience, we posit that the optimal therapeutic approach for treating PFE in specific patient subpopulations is minimally invasive surgery.…”
Section: Discussionsupporting
confidence: 59%
“…Among these approaches, the upper hemi-sternotomy method is widely employed and considered effective [ 1 ]. Additionally, the Right Anterior Thoracotomy Approach has been reported as a successful technique for excising PFE located on the aortic valve [ 13 ]. Furthermore, some institutions employ completely endoscopic techniques, whether robotic or non-robotic, to achieve PFE removal from the aortic valve [ 12 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our observations suggest that the utilization of the minimally invasive approach in the management of PFE yielded positive outcomes in these two cases. In comparison to other authors, the length of hospitalization observed in our study is nearly equivalent [1,13]. In our experience, we posit that the optimal therapeutic approach for treating PFE in speci c patient subpopulations is minimally invasive surgery.…”
Section: Discussionsupporting
confidence: 57%
“…While median sternotomy remains the predominant surgical approach, recent evidence suggests that minimally invasive techniques can provide favorable exposure and safe resection, particularly for aortic or tricuspid valve PFE, when there is no co-existing pathology necessitating open cardiac surgical intervention [1,2,6,8,[12][13][14][15]. Minimally invasive surgery offers several potential bene ts, such as improved cosmesis, decreased post-operative pain, reduced blood loss and subsequent need for transfusion, as well as shorter intensive care unit and overall hospital stay [1].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical resection has traditionally been performed using cardiopulmonary bypass via median sternotomy. Recently, minimal invasive techniques have been employed to that goal, including thoracoscopic [ 23 , 24 ] or robotic access [ 25 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%